'An Alligator Got Betty': Dangerous Animals as Historical Agents. (1st May 2018) - Maglen, Krista
Abstract : In 1932 four year old Betty Doherty was taken from the grasp of her older brother by a fourteen-foot crocodile in Far North Queensland. Through an examination of historical sources as well as the work of psychologists, cognitive scientists and zoologists, this paper explores the role ascribed to the crocodile as well as other 'dangerous' animals that have bitten, stung or consumed settlers across Australia, and asks whether and how they might 'act' or be given voices within our reading and understanding of the past. Animal historians have begun to ask questions about historical agency through analyses of domesticated or working animals, and interactions between people and wild mammals. Insects, fish and reptiles, however, remain anonymous and non-specific, disappearing back beneath the waves or into the dark holes from which they emerged, and yet they were often agents of great change in the human lives they encountered. This paper asks whether historical agency and intent can be found in these less sympathetic and less 'knowable' creatures, and examines how historians might conceive of watery predators or venomous creatures that disappeared from sight or perhaps were never seen at all.